Effect of interculture operations and scheduling of Atrazine application on weed control and productivity of rainfed maize (Zea mays) in Shiwalik foothills of Punjab - SHARMA, A R; TOOR, A S; SUR, H S (The Indian Journal of Agricultural Sciences, 2013)
In a 2-year study during 1997 and 1998, the effect of interculture operations at 15 and 30 days of growth integrated withn atrazine @ 1 kg/ha as pre- and post-emergence through either spray or sand-mix application was evaluated on rainfed maize (Zea mays L.) at Ballowal Saunkhri, Punjab. Results showed that atrazine applied as pre-emergence reduced weed population at 15 days of growth significantly (74.8-83.6%) compared with control (75-80 no./m2). Post-emergence application of Atrazine at 15 days of growth after interculture (hoeing) caused a similar reduction (77.1-82.9%) in weed population at 30 days of growth. Atrazine application through spray or sand-mix was equally effective in controlling weeds and increasing grain yield equal to that with Atrazine+interculture at 15 days of growth. Earthing-up not found beneficial in atrazine-applied treatments. The loss in grain yield due to unchecked weed growth was to the extent of 32.4-42.3%. The results suggested that atrazine can be useful as sand mix post-emergence application following hoeing at 15 days of growth for effective control of weeds and increasing grain yield of maize by 1.0 tonne/ha in the Kandi area of Punjab